Student’s Concept Understanding and Motivation to Learn Through Flipped Classroom Learning Integrated with Nested Model - Aisyah Jiyantika Gitadewi; Prabowo; Zainul Arifin Imam Supardi; Wiwien Maryuni (Studies in Learning and Teaching, 2022)
This research aimed to describe the effectiveness of the flipped classroom integrated with nested model in student’s concept understanding and motivation to learn. The research type is quasi-experiment with one-group pretest-posttest design. The research was given to 20 students in VII-D class of SMPN 21 Surabaya. The effectiveness of the flipped classroom integrated with nested model was obtained from the results of a concept understanding test and a motivation to learn questionnaire. The student's concept understanding test showed that there was an improvement in gain scores between the pretest and posttest scores which is medium category and 90% of students were declared complete. Meanwhile, the gain score on the completeness of the concept understanding indicator was high category. Then the results of the student’s motivation to learn showed that there was an improvement in gain scores between pretest and posttest which is medium category. The data obtained that flipped classroom integrated with nested model was effective as a learning instrument to improve student’s concept understanding and motivation to learn during the Covid-19 pandemic.